A one-year descriptive epidemiology of zoonotic abortifacient pathogen bacteria in farm animals in Turkey. (August 2021) - Sakmanoğlu, Aslı; Uslu, Ali; Sayın, Zafer; Gölen, Gökçenur Sanioğlu; İlban, Ayşegül; Padron-Perez, Beatriz; Karyeyen, Yasemin; Gök, Ayten; Tekindal, Mustafa Agah; Erganis, Osman
Highlights: The prevalences of bacteria were significantly different as source, sampling periods, and regions. The frequency of zoonotic pathogens was the highest in the aborted calf samples. The development of alternative strategies is crucial in the decrease of infectious abortion rates. Abstract: This study aimed to investigate the epidemiology of 10 suspicious pathogenic bacteria in 250 stomach contents of aborted calf, lamb, and goat foetuses in 2019. The 155 positive samples obtained from PCR consisted of 53 (58.88 %) bacteria from 90 lamb samples, 10 (43.47 %) bacteria from 23 goat samples, and 92 (67.15 %) bacteria from 137 calf samples. The five most common bacteria associated with abortions were Brucella melitensis, 52 (20.9 %); B. abortus, 13 (5.2 %); Leptospira spp., 34 (13.6 %); Campylobacter fetus, 52 (20.9 %); and Coxiella burnetii, 4 (1.6 %). The highest rate of B. melitensis (65.4 %), B. abortus (69.2 %), Leptospira spp. (67.6 %), and C. fetus (50 %) was detected in the aborted calf samples. The highest individual rate was that of C. fetus (5.2 %). The flock-herd rates of B. melitensis, B. abortus, Leptospira spp., C. fetus, and C. burnetii infections in the 29 farms studied were 34.48 %, 20.69 %, 62.06 %, 82.75 %, and 3.44 %, respectively, with a confidence level and interval of 95 %. The frequency of abortions caused by Leptospira spp. and Campylobacter fetus may be related to increasing in B. melitensis . The rates of aborted calf, lamb, and goat foetuses among the various sampling periods and regions were significantly (P < 0.01) different. In conclusion, precautions should be applied to reduce the spread of these bacterial agents in high-risk areas and to eliminate the risk of harbouring these zoonotic infections in humans. Therefore, these results must be taken into account in the development of control and protection strategies against abortions in animals.